STRATEGIES FOR DEVELOPING HEALTHY LIFESTYLE HABITS AMONG YOUTH THROUGH SPORTS TOURISM - Aslanova Maloxat Akramovna (SCIENCE AND CULTURE: INNOVATIONS OF THE 21ST CENTURY, 2026)
This article analyzes the role of sports tourism in developing healthy lifestyle habits among young people. It highlights effective strategies for increasing physical activity, strengthening psychological well-being, and enhancing social engagement through sports tourism activities. The study also discusses practical approaches to motivating youth participation and integrating sports tourism into educational and social development programs.